Online Versus Face-to-Face Training of Critical Time Intervention: A Matching Cluster Randomized Trial. Issue 4 (1st October 2016) - Olivet, Jeffrey; Zerger, Suzanne; Greene, R. Neil; Kenney, Rachael R.; Herman, Daniel B.
ABSTRACT: This study examined the effectiveness of online education to providers who serve people experiencing homelessness, comparing online and face-to-face training of Critical Time Intervention (CTI), an evidence-based case management model. The authors recruited 184 staff from nineteen homeless service agencies to participate in one of two training conditions: (a) Online Training + Community of Practice or (b) Face-to-Face Training + Telephone Consultation . Each group received twenty-four hours of instruction and support. Through baseline, follow-up, and nine-month posttraining surveys, the authors examined satisfaction, knowledge gains, knowledge retention, and readiness to implement CTI. Although satisfaction rates were higher among participants in the face-to-face group, the two training conditions produced comparable pre/postknowledge gains. Furthermore, both groups showed increased knowledge retention scores at nine-month follow-up, with the online group scoring higher than the face-to-face group.